Synthesis of SnO2 Using Hydrothermal Method and Its Application as Catalyst in Esterification of Oleic Acid - Soni Setiadji; Ridha Ulfah; Ira Ryski Wahyuni (Department of Chemistry Faculty of Science and Technology Walisongo, 2021)
Biodiesel is currently getting great attention because it can reduce carbon dioxide emissions by 78.5% compared to petroleum-based diesel. The reaction that can produce biodiesel is the esterification reaction with the addition of a heterogeneous catalyst, one of which is SnO2 which can be used as Lewis acid for the esterification reaction. In our study, SnO2 has been successfully synthesized and then succeeded in reducing the level of oleic acid FFA (Free Fatty Acid) through an esterification reaction. SnO2 was synthesized from SnCl2.2H2O using the hydrothermal method with the addition of CTAB (Cetyl Trimethyl Ammonium Bromide) as a capping agent which was then analyzed using XRD (X-Ray Diffraction) and SEM (Scanning Electron Microscopy). The catalytic activity of the SnO2 sample was carried out through the esterification reaction of oleic acid in ethanol at 65 °C for 6 hours with variations in catalyst weight and variations in the ethanol mole ratio. From XRD analysis, SnO2 sample consists of cassiterite minerals and has typical peaks at 2θ = 26.56°; 33.84°; 37.92°; 38.90°; 42.53°; 51.64°; 54.66°; 57.76°; 61.68°; 62.34°; 64.60°; and 65.88° with the highest intensity at 2θ = 33.84°. During condition optimization of esterification reaction of oleic acid, variations in the weight of SnO2 catalyst resulting from the optimum FFA level could be reduced by 75.05%, whereas to variations in the mole ratio of ethanol, the optimum FFA level could be reduced by 85.53%. In our study, SnO2 has been successfully synthesized and then succeeded in reducing the level of oleic acid FFA through esterification reaction until 85.53%.